Analisis Peluang, Ancaman, dan Solusi Perdagangan Internasional Indonesia di Sektor Perkebunan serta Pengaruh Kebijakan Non Tarif Indonesia dan Negara di Asia - Dea Puspita Sari (Jurnal Ekonomi dan Bisnis Digital, 2026)
International trade in Indonesia's plantation sector faces complex dynamics amid projected global growth until 2025. This study analyzes opportunities, threats, and strategic solutions for Indonesia's tea exports through a comparative case study with Malaysia, and analysis of secondary data from the Central Statistics Agency (BPS), the Indonesian Ministry of Trade, as well as the International Tea Committee (ITC) report for the 2020-2024 period. The results show key opportunities for Indonesia including demand for organic premium markets in Europe and the Americas (projected to increase 15% by 2025), RCEP policy support, and arable land superiority in West Java and Sumatra. However, significant threats include stiff competition from Malaysia which excels in halal certification and supply chain efficiency (Malaysia's exports are up 12% YoY), fluctuations in global commodity prices due to climate change, and non-tariff barriers such as EU Green Deal standards. The recommended solutions include diversification of value-added products (such as ready-to-drink packaged tea), increased sustainability certification (Rainforest Alliance), post-harvest technology investment, and Indonesia-Malaysia bilateral collaboration for ASEAN common markets. The implementation of this solution has the potential to increase Indonesia's tea export share by 20% by 2025, supporting national economic resilience.